2020
DOI: 10.1101/2020.02.03.932244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toward an integrated classification of neuronal cell types: morphoelectric and transcriptomic characterization of individual GABAergic cortical neurons

Abstract: Neurons are frequently classified into distinct groups or cell types on the basis of structural, physiological, or genetic attributes. To better constrain the definition of neuronal cell types, we characterized the transcriptomes and intrinsic physiological properties of over 3,700 GABAergic mouse visual cortical neurons and reconstructed the local morphologies of 350 of those neurons. We found that most transcriptomic types (t-types) occupy specific laminar positions within mouse visual cortex, and many of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 69 publications
(114 reference statements)
1
40
0
Order By: Relevance
“…3a, right). Relatively few genes (177 genome-wide) showed enriched expression in dissociated nuclei relative to Patch-seq cells, suggesting that high quality transcriptomes collected in this data set do not show the increased dropout rate reported in our previous study 32 . This is likely because we are comparing our human Patch-seq cells to a reference of dissociated human nuclei, rather than dissociated mouse cells.…”
Section: Resultssupporting
confidence: 42%
See 3 more Smart Citations
“…3a, right). Relatively few genes (177 genome-wide) showed enriched expression in dissociated nuclei relative to Patch-seq cells, suggesting that high quality transcriptomes collected in this data set do not show the increased dropout rate reported in our previous study 32 . This is likely because we are comparing our human Patch-seq cells to a reference of dissociated human nuclei, rather than dissociated mouse cells.…”
Section: Resultssupporting
confidence: 42%
“…The subset of neurons (109) with sufficient biocytin labeling and intact apical dendrites were imaged at high resolution, then subsequently manually reconstructed based on the image. L2/3 pyramidal neurons from mouse visual cortex were analyzed using the same Patch-seq platform 32 , resulting in 120 neurons with high-quality electrophysiology and transcriptome data mapping to the three L2/3 glutamatergic t-types, and 60 neurons with data in all three modalities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…morphology, physiology, or molecular expression) to using a combination of these properties in a multimodal fashion 41 . Recent studies have demonstrated the power of this multimodal approach to curate and refine definitions of inhibitory and excitatory neuronal cell types in visual cortex 42,43 . Similarly, our multimodal strategy for measuring morphology, molecular markers, and connectivity can be also applied towards refining cell type definitions across the brain.…”
Section: Discussionmentioning
confidence: 99%